Recombinant production of active Streptococcus pneumoniae CysE in E. coli facilitated by codon optimized BL21(DE3)-RIL and detergent. Issue 4 (21st April 2019) - Verma, Deepali; Antil, Monika; Gupta, Vibha
Abstract: The emergence of drug resistance in Streptococcus pneumoniae (Spn) is a global health threat and necessitates discovery of novel therapeutics. The serine acetyltransferase (also known as CysE) is an enzyme of cysteine biosynthesis pathway and is reported to be essential for the survival of several pathogenic bacteria. Therefore, it appears to be a very attractive target for structure–function understanding and inhibitor design. This study describes the molecular cloning of cysE from Spn in the pET21c vector and efforts carried out for expression and purification of active recombinant CysE. Significant expression of recombinant Spn cysE could be achieved in codon optimized BL21(DE3)-RIL strain as opposed to conventional BL21(DE3) strain. Analysis of codon adaptation index (CAI) with levels of eukaryotic genes and prokaryotic cysEs expressed in heterologous E. coli host suggests that codon optimized E. coli BL21(DE3)-RIL may be a better host for expressing genes with low CAI. Here, an efficient protocol has been developed for recovery of recombinant Spn CysE in soluble and biologically active form by the usage of nonionic detergent Triton X-100 at a concentration as low as 1%. Altogether, this study reports a simple strategy for producing functionally active Spn CysE in E. coli .